2022
DOI: 10.3390/ijerph19127504
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking in Informal Family Caregivers of People with Dementia: A Qualitative Study with iSupport as a Case in Point

Abstract: Supportive measures and training interventions can improve the care of people with dementia and reduce the burden on informal caregivers, whose needs remain largely unmet. iSupport is an evidence-based online intervention developed by the World Health Organization to provide support and self-guided education to informal family caregivers of people with dementia. This qualitative study explored barriers and facilitators in the access and use of supportive measures for family caregivers of people with dementia l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…The results add voice to other research that has found the service closures during the pandemic had a negative impact on carers, leading to increased loneliness, declining mental health, and reduced feelings of wellbeing [ 9 , 22 , 31 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results add voice to other research that has found the service closures during the pandemic had a negative impact on carers, leading to increased loneliness, declining mental health, and reduced feelings of wellbeing [ 9 , 22 , 31 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 74%
“…Research on experiences during the COVID-19 pandemic have consistently reported that informal carers experienced isolation, loneliness, and declines in physical and mental health and wellbeing [ 1 , 3 , 30 , 31 ]. Doody and Keenan’s [ 32 ] scoping review reported that, during the pandemic, people living with intellectual disability and their carers were particularly vulnerable to negative physical, social, and psychological impacts.…”
Section: Introductionmentioning
confidence: 99%
“…These findings confirm the need for ongoing training for family/informal caregivers to improve access to services [40], increase well-being [41,42] and self-efficacy [43], and improve their QoL [44].…”
Section: Discussionsupporting
confidence: 66%
“…We prompted and collected suggestions for improvement, as also recommended by the WHO guidelines. In addition, we decided to expand our inquiry to caregivers’ attitudes toward support measures and help-seeking behaviors, which we have previously reported in detail elsewhere [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data management and coding processing were facilitated by NVivo 12 software (Lumivero) [ 41 ]. Additional methodological details have been previously reported [ 40 ].…”
Section: Methodsmentioning
confidence: 99%